Public health emergency literacy among adult residents of Zhuhai city: a cross-sectional survey and structural equation modeling analysis - Zhaoguang ZUO; Zhuqing CHEN; Jun'an LIU; Qin AO (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo explore the status and interrelations of knowledge, attitude, and behavior about public health emergency among adult residents in Zhuhai city, Guangdong province using structural equation modeling analysis. MethodsA face-to-face interview and a complementary online survey were conducted among 2 201 permanent residents aged 16 - 99 years recruited through cluster sampling from businesses, institutions, factories, and communities in Zhuhai city from April 2022 to April 2023. Participants' public health emergency literacy information was collected using a self-designed questionnaire based on 12 items of the Citizen Public Health Emergency Literacy Entry developed by the China Population Communication Center of the National Health Commission. Using AMOS 26.0, a structural equation model of residents' public health emergency literacy was constructed to analyze the mutual influences among different dimensions of public health emergency literacy. ResultsAmong 2013 participants with valid information, the proportion with public health emergency literacy (total score ≥ 36 on a full scale of 45) was 57.53%, and the proportion with public health emergency knowledge, attitude, and behavior literacy was 34.08%, 69.35%, and 60.76%, respectively. Knowledge literacy had a positive effect on both attitude and behavior literacy (βknowledge→attitude = 0.58, βknowledge→behavior = 0.46, P < 0.001), and the effect of attitude literacy on behavior literacy (βattitude→behavior = 0.47) was greater than that of knowledge literacy (βknowledge→behavior = 0.46, P < 0.001). ConclusionThe overall level of public health emergency literacy among adult residents of Zhuhai city is relatively high, with public health emergency attitudes having a stronger influence on emergency behaviors than knowledge. It is urgent to establish a system of normalized public health emergency education for all citizens in Zhuhai city to utilize the mediating mechanism of public health emergency attitudes in positively transforming public health emergency knowledge into behaviors.